Low-complexity frequency-invariant beampattern synthesis using accurate response control for speech extraction - Xu, Jiayi; Li, Jian; Meng, Weixin; Li, Xiaodong; Zheng, Chengshi (Applied acoustics, 2024)
Beampattern synthesis generally designs weight parameters to form a main beam towards the direction of interest while suppressing interference and environmental noise simultaneously, playing a critical role in fixed beamforming techniques. In practical applications, when the position of the interference source changes, the filter design requirements will correspondingly change, thus necessitating accurate response control and rapid update capabilities. A low-complexity method is also highly desired in broadband beampattern synthesis, especially for time-domain beamformers with a relatively large number of weight parameters. To achieve rapid update and reduce the complexity for time-domain beamformers, this paper proposes a low-complexity frequency-invariant beampattern synthesis method using accurate response control. By introducing the null-forming scheme of adaptive beamformers, a virtual interference-plus-noise covariance matrix is constructed to precisely control the beampattern. Additionally, the spatial response variation is considered in the optimization problem for a constant mainlobe pattern, avoiding the complexity of determining a desired beampattern. Compared with the existing algorithms based on the interior-point method and the alternating direction method of multipliers, the proposed method reduces the computational complexity of each iteration, showing higher efficiency in broadband beampattern synthesis. Furthermore, the proposed method adjusts the beamformer flexibly on the basis of a pre-designed beampattern, achieving fast beampattern update when the acoustic environment changes. Numerical simulations on beam patterns and experimental results on speech extraction demonstrate better interference suppression performance of the beamformers designed by the proposed method. •Low-complexity frequency-invariant beampattern synthesis can be realized using accurate response control.•The computational complexity is significantly reduced, especially when dealing with a large number of microphones.•The designed beamformer is effective and demonstrates impressive performance in speech extraction.